1998
DOI: 10.1590/s0004-282x1998000400017
|View full text |Cite
|
Sign up to set email alerts
|

Epidural hematoma after ventriculoperitoneal shunt surgery: report of two cases

Abstract: ABSTRACT-Ventriculoperitoneal shunt operations represent the most used choice for treating hydrocephalus, although some related complications have been reported. Due to its rarity, potential dangers, and mortality rate, we present two cases of epidural hematoma following ventriculoperitoneal shunt, discussing its pathophysiology and prophylaxis.KEY WORDS: epidural hematoma, complications, cerebrospinal fluid shunts. Hematoma epidural após derivação ventriculoperitoneal: relato de dois casosRESUMO -No tratament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…An EDH can develop regionally; adjacently; or distantly, in a remote area that is removed from the operation site [ 1 ]. There are some reports of remote EDHs that occurred after a ventriculo-peritoneal shunt operation [ 3 4 5 6 7 8 9 10 11 12 13 14 ] or a decompressive craniectomy [ 15 16 ]. Few cases of postoperative remote EDHs after brain tumor surgery have been reported [ 2 17 18 19 20 21 22 23 ], especially in posterior fossa surgery [ 24 25 26 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…An EDH can develop regionally; adjacently; or distantly, in a remote area that is removed from the operation site [ 1 ]. There are some reports of remote EDHs that occurred after a ventriculo-peritoneal shunt operation [ 3 4 5 6 7 8 9 10 11 12 13 14 ] or a decompressive craniectomy [ 15 16 ]. Few cases of postoperative remote EDHs after brain tumor surgery have been reported [ 2 17 18 19 20 21 22 23 ], especially in posterior fossa surgery [ 24 25 26 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of epidural hematoma after ventricular shunt operation was 5.6% in adults and 0% in children before the advent of valve-regulated shunt (1). In our knowledge, 15 acute and 7 chronic cases of epidural hematomas were reported after valve-regulated shunt placement in the literature (2,3,5,(10)(11)(12). Epidural hematoma often becomes symptomatic soon after a neurosurgical operation, whereas diagnosis can be procrastinated in a case of an efficient shunt which helps reduce intraventricular pressure and volume.…”
Section: Discussionmentioning
confidence: 99%
“…13 EDH complications generally arise within a few hours after the operation, but the time cited in the literature ranges from a few hours to even 3 years after surgery. 16,17 The symptoms arise rapidly in cases of acute EDH; however, if the bleeding is slow, patients can remain asymptomatic, delaying diagnosis and resulting in adverse outcomes. 10 Byrappa et al suggested two reasons for such a delay.…”
Section: Discussionmentioning
confidence: 99%